A study on the L1 optimal PD controller with application to joint motion control of a robot manipulator - Kim, J.H.; Hur, S.-M.; Lee, J.; Oh, Y. (Proceedings - IEEE International Conference on Robotics and Automation, 2016)
In this paper, we consider the L1 optimal proportional-derivative (PD) controller synthesis by which the L∞ gain of trajectory tracking systems can be reduced. The notion of input-to-state stability (ISS), which has been equipped with the L2 norm of a vector-valued signal, plays important roles in evaluating the effect of disturbances on the system states. In connection with this, we first redefine the conventional ISS with the L∞ norm to deal with bounded persistent disturbances because the disturbances should be mathematically regarded as elements of the L∞ space. A tractable model for trajectory tracking control of robot systems is then given by using ideas of extended disturbance and composite error. We next introduce a design method of the L1 optimal PD controller for such a model, by which the trajectory tracking system satisfies the redefined ISS and the L∞ gain is less than a performance level γ. Finally, we examine the effectiveness of the design method through experimental results for a typical robot manipulator. ？ 2016 IEEE.